Model for monitoring socioenvironmental conflicts in relation to the emission of particulate matter in the prehauling phase of a surface mine in Peru - Filomeno, Marcio (2019)
El texto completo de este trabajo no está disponible en el Repositorio Académico UPC por restricciones de la casa editorial donde ha sido publicado.